2021
DOI: 10.1177/20552173211028875
|View full text |Cite
|
Sign up to set email alerts
|

Forearm muscle mitochondrial capacity and resting oxygen uptake: Relationship to symptomatic fatigue in persons with multiple sclerosis

Abstract: Background Mitochondrial dysfunction has been implicated in the pathogenesis of multiple sclerosis (MS). Whether mitochondrial alterations are a function of ambulatory dysfunction or are of a non-ambulatory systemic nature is unclear. Objective To compare oxidative capacity, and rest muscle oxygen consumption (mVO2) in the upper limb of persons with multiple sclerosis (PwMS) to a control group (CON), whereby an upper limb would be comparatively independent of ambulation or deconditioning. Methods Near infra-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Whereas, deconditioning can be expected to be prominent in the leg muscles of MS patients with impaired ambulation, one would not expect it to occur in non-affected upper extremity muscles. Thus, the results of two recent studies that demonstrated reduced oxidative capacity in both leg (gastrocnemius) and wrist flexor muscles of MS patients compared to controls raise a challenge to the deconditioning hypothesis ( 99 , 100 ).…”
Section: Current Concepts Of Motor Fatigue In Ms: Definitions Assessm...mentioning
confidence: 99%
“…Whereas, deconditioning can be expected to be prominent in the leg muscles of MS patients with impaired ambulation, one would not expect it to occur in non-affected upper extremity muscles. Thus, the results of two recent studies that demonstrated reduced oxidative capacity in both leg (gastrocnemius) and wrist flexor muscles of MS patients compared to controls raise a challenge to the deconditioning hypothesis ( 99 , 100 ).…”
Section: Current Concepts Of Motor Fatigue In Ms: Definitions Assessm...mentioning
confidence: 99%